Fuzzy System for the Quality Assessment of Educational Multimedia Edition Design - Vsevolod Senkivskyy; Liubomyr Sikora; Nataliia Lysa; Alona Kudriashova; Iryna Pikh (Applied Sciences)
The quality of educational multimedia edition design is determined by a set of characteristics that affect perception, readability and communication efficiency. Quality assessment of multimedia edition design is based on a comprehensive analysis of characteristics that affect the quality of output data, edition processing and content representation. Within the framework of this study, the goal is to develop a methodology for assessing the quality of educational multimedia edition design using fuzzy logic. An approach to determining an integral quality indicator based on fuzzy logic is proposed, which ensures that the influence of various factors which are difficult to characterize exclusively by numerical parameters, is taken into account. A multilevel model of fuzzy logical inference is constructed, representing the dependency between quality factors. Membership functions for linguistic variables are formed and their weight coefficients are determined using pairwise comparison matrices. The developed approach contributes to making informed management decisions in the process of creating multimedia products. The use of fuzzy logic methods allows one to assess the design quality even under conditions where the parameters are subjective or do not have clear numerical characteristics. Thus, quality prediction provides the opportunity to identify the design weaknesses at the stage of its development, optimize the process of creating multimedia editions, and increase the efficiency of their use in educational and professional environments. Further research aimed at integrating artificial intelligence for automated updating of the knowledge base and expanding the system by introducing additional assessment criteria is considered to be promising.